Visual Communication: Case Study On The Visual Approach In Child Sexual Abuse Awareness Campaign (Print Ads) - Pahme, Nur Faizah Mohd (2019)
Between the year 2011 to 2016, 5502 cases of child sexual abuse (CSA) with almost 80% offenders are close to the victims have been reported. CSA has become a huge problem and needs attention from the government. Therefore, in order to prevent this issue, society’s awareness is required. In Malaysia, a various range of awareness campaign has been used nationally as well as internationally. The ‘Hentikan!!: Jenayah Seksual Kanak-Kanak’ campaign is an example of campaign executed by the government and the NGOs. It aims to build up the commitment and awareness of the society. However, the existing awareness campaign’s visual used are mostly hard-sell and not related to the child sexual abuse issue, which focusing on photos of children. Hence, this study aims to investigate the visual approach used in the CSA awareness campaign, where it focuses on the print ads. Therefore, the research will employs qualitative research design, which involved two samples – design agencies and also academician. The main purpose of this research is to identify and define the findings. Both samples are significant to this study so that both designers and academic researcher are able to design and define the right strategy to be used in executing the campaign.